Our friend [videorecording (DVD)] - Cowperthwaite, Gabriela; Segel, Jason, 1980-; Johnson, Dakota, 1989-; Affleck, Casey, 1975-; Teague, Matthew (Universal Pictures Home Entertainment, 2021)
Follows Matt and Nicole Teague and their two young daughters after Nicole is diagnosed with terminal cancer and the couple's best friend puts his life on hold to stay with them for help and support.